An Aboriginal Women's Song from Arrwek, Central Australia. Issue 2 (3rd July 2018) - Yeoh, Calista; Turpin, Myfany
Abstract : Songs are a fundamental part of Indigenous Australian cultures. They are vehicles for transmitting experiences about a region, including the stories and ancestral entities from the creation. Yet relatively little is known about the musical characteristics of songs from many parts of Australia. In this article we present the first musical analysis of traditional songs of the Anmatyerr people of central Australia. We analyse a selection of songs from recordings of a women's song set owned and performed by the landholders of Arrwek, an estate that straddles the Anmatyerr-speaking and Warlpiri-speaking regions. We analyse three basic acoustic elements of a central Australian Aboriginal song: rhythmic text, pitch, and the relationship between them. Our analysis finds that these have much in common with Warlpiri songs, despite their Anmatyerr geographic affiliation.